Operations now: profitability, processes, performance - Byron Finch (McGraw Hill Irwin, 2006)
Berisi : 1. Chapter menu 2. Content menu yang berisi : 14 videos, intractive models, excel tutor, interactive quizzes, visit the online learning center, visit the operations management center.